Breeding Phenology of Red-Shouldered Hawks (Buteo lineatus) Is Related to Snow Cover and Air Temperature During the Pre-Laying Period - Dykstra, Cheryl R.; Hays, Jeffrey L.; Simon, Melinda M.; Wegman, Ann R. (Frontiers in Ecology and Evolution, 2021)
Global climate change has advanced the breeding phenology of many avian species. However, raptors’ breeding phenologies may not respond in the same way to the factors that influence passerine breeding dates. We studied reproduction of suburban and rural Red-shouldered Hawks (Buteo lineatus) in southern Ohio, United States, from 1997 to 2020. Mean hatching dates for 786 broods were 24 April [Julian day: 114.1 ± 0.3 d (SE)] for suburban birds and 25 April (Julian day: 114.5 ± 0.4) for rural birds. Egg-laying date averages approximately 33 days before hatching date, or about the third week of March. We used mixed models to test which factors influenced nestling hatching dates from 1997 to 2020. The best model included year, days of snow cover during the pre-laying period (February–March), and mean March temperature, with days of snow cover having the largest effect. Hatching date (in Julian days) was positively related to snow cover and negatively related to air temperature, i.e., young hatched earlier in years with fewer days of snow cover and in warmer years). Young also hatched slightly later as the study progressed. Overall, neither mean hatching date nor any of the weather variables showed a significant trend over the course of the study. Previously published reports indicate that many raptor species do not exhibit advancing hatching dates, and breeding phenologies often reflect local weather conditions. The complexity and diversity of raptor responses to climate change underscore the importance of long-term studies of raptors at multiple locations.